The Impact of Liver Metastasis on Anti-PD-1 Monoclonal Antibody Monotherapy in Advanced Melanoma: Analysis of Five Clinical Studies - Wang, Xuan; Ji, Qing; Yan, Xieqiao; Lian, Bin; Si, Lu; Chi, Zhihong; Sheng, Xinan; Kong, Yan; Mao, Lili; Bai, Xue; Tang, Bixia; Li, Siming; et al. (Frontiers in Oncology, 2020)
Anti-programmed cell death protein 1 (PD-1) monoclonal antibody therapy is becoming a standard treatment for advanced melanoma that produces durable responses and prolonged survival, but the prognosis of patients with liver metastases is still unsatisfactory. Here, we analyzed five clinical studies (second-line or later, JS001-I-PK, CT4, KN151, BGB-A317-102, and SHR-1210-102; performed between 2015 and 2018) of anti-PD-1 monotherapy for advanced melanoma to explore prognostic variables for patients with liver metastases. A total of 168 patients with stage IV melanoma were included, among which 47 had liver metastasis and 121 did not. The objective response rate (ORR) of the no liver metastasis group was significantly higher than that of the liver metastasis group (20.7 vs. 4.3%, P < 0.05). The median progression-free survival (PFS) time was 3.6 months for the patients with liver metastasis and 7.4 months for those without liver metastasis (P < 0.05). The no liver metastasis group also had a longer median overall survival (OS) time than the liver metastasis group (22.8 vs. 15.7 months, P < 0.05). Multivariate analysis showed that liver metastasis was negatively associated with PFS. In the liver metastasis group, compared to metastases in other sites (lymph node, subcutaneous, and lung), liver metastases responded worse to anti-PD-1 monotherapy and were most likely to progress. Intrahepatic progression (defined as an increase in liver metastasis by more than 20% from baseline or having new liver metastases, P < 0.05) was negatively associated with OS, which indicates the need to find a more effective therapy that can target liver metastases. Interestingly, with a median PFS and OS time of 6.0 and 30.9 months, respectively, previous oncolytic virotherapy might bring more benefits to patients with liver metastasis, but confirmation is needed because of the limited number of samples. These findings emphasize that liver metastasis is a poor prognostic factor for advanced melanoma treated with anti-PD-1 monotherapy. Further exploration is still needed to find a new treatment approach for these patients.